2004
DOI: 10.1590/s1415-47572004000300014
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome study of Anteaters (Myrmecophagideae, Xenarthra): a preliminary report

Abstract: Anteaters belong to the Order Xenarthra / Family Myrmecophagidae and are the only members without teeth. There are three genera with four living species in the family Myrmecophagidae: Myrmecophaga tridactyla (giant anteater), Tamandua tetradactyla (southern lesser anteater), Tamandua mexicana (northern lesser anteater), and Cyclopes didactylus (silky anteater). The karyotypes of M. tridactyla (2n = 60), T. tetradactyla (2n = 54) and C. didactylus (2n = 64) have already been described. In the present paper, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The chromosomes of Xenarthra are still poorly studied and most of the described karyotypes were analyzed after conventional staining, without banding patterns [28-30]. The diploid numbers in Xenarthra range from 2n = 38 in the armadillo Tolypeutes matacus to 2n = 65 in the sloth Choloepus didactylus [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…The chromosomes of Xenarthra are still poorly studied and most of the described karyotypes were analyzed after conventional staining, without banding patterns [28-30]. The diploid numbers in Xenarthra range from 2n = 38 in the armadillo Tolypeutes matacus to 2n = 65 in the sloth Choloepus didactylus [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…A new karyotype with 2n = 56 was recently reported in 1 male anteater from southeastern Brazil and suggested to belong to a still undescribed third species of Tamandua [Pereira Jr. et al, 2004]. On the other hand, Gardner [2008] suggested that this new complement is likely to be that of T .…”
Section: Anteatersmentioning
confidence: 99%
“…A summary of the available karyotypic data of Xenarthra is presented in table 1 . Chromosome rearrangements, such as pericentric inversions, Robertsonian fusions/fissions and heterochromatin additions/deletions, have been suggested to explain the karyotypic evolution in Xenarthra [Jorge et al, 1977[Jorge et al, , 1985aBarroso and Seuánez, 1991;Pereira et al, 2004]. Nevertheless, their occurrence remains speculative, as the suggestions were based on conventionally stained chromosomes or low resolution banding patterns.…”
Section: Classical Cytogenetics Of Xenarthramentioning
confidence: 99%
See 2 more Smart Citations